2021
DOI: 10.1097/md.0000000000025846
|View full text |Cite
|
Sign up to set email alerts
|

Composite hemangioendothelioma of the spleen with multiple metastases

Abstract: Composite hemangioendothelioma (CHE) is a rare vascular neoplasm of intermediate malignant potential. Only 52 cases have been reported in the English literature, and one case previously reported occurred in the spleen. The purpose of our study was to report a 65-year-old man diagnosed as CHE primary arising from the spleen with multiple metastases.Clinical and imaging features, laboratory tests, and pathological results about CHE were described in detail in this study.The patient presented with multiple lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Composite hemangioendothelioma (CHE) was first described in 2000 by Nayler et al [ 2 , 5 , 7 9 ]. It is a rare intermediate-grade (occasionally metastatic) vascular tumor that is most often seen in young adults (mean age 42 years) but can present at any age from birth to 75 years, with women being the most common [ 5 , 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite hemangioendothelioma (CHE) was first described in 2000 by Nayler et al [ 2 , 5 , 7 9 ]. It is a rare intermediate-grade (occasionally metastatic) vascular tumor that is most often seen in young adults (mean age 42 years) but can present at any age from birth to 75 years, with women being the most common [ 5 , 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as a locally aggressive, occasionally metastatic vascular tumor containing a mixture of histologically distinct components [ 4 ]. CHE is very rare, with about 59 cases reported in the English literature so far [ 5 ]. Herein, we report two cases of CHE, the first case occurred in the left pubis (female, 21 years old), and the second case is a patient post-resection of CHE in the manubrium sterni 10 years ago [ 1 ], who developed of new lesions in the left ilium and T6, T12 vertebra (male, 66 years old).…”
Section: Introductionmentioning
confidence: 99%
“…Benign, neutral, and malignant components are histologically mixed with each other, as in our case, making it difficult to identify those components. So far, fewer than 60 clinical cases have been reported [Li 2021]. It commonly has occurred as long-standing lesions in the dermis and subcutis of the extremities but also increasingly has been reported at other sites, including the oral cavity, mediastinum, manubrium sterni, and in viscera such as the kidney and spleen [Chen 2012].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature identified a total of 52 patients with CHE (mean age: 42.5 years) reported in the English language, including a 48-year-old woman with CHE in the spine [12]. Most patients underwent surgical treatment.…”
Section: Et Al Reported Thatmentioning
confidence: 99%
“…Most patients underwent surgical treatment. Radiotherapy, chemotherapy, electron beam irradiation, interferon-α 2b, and thalidomide have also been described as effective for CHE with or without resection, although are less common than surgery [12][13][14][15][16][17]. Since CHE in the spine or bones is rare, there remains no consensus on its treatment [13,14].…”
Section: Et Al Reported Thatmentioning
confidence: 99%